Deriving an indoor environmental index for portuguese office buildings - Gomes, João (2017)
In 2002, the European Commission (EU) issued a Directive aiming to reduce the energy consumption of buildings, which was adopted by the EU member states and came into force in 2006. Portugal adopted it by issuing law decrees in 2006 which considered not only the energy saving aspects but also additional specific measures aiming to protect indoor air quality (IAQ). This new legislation is now being enforced, and it will be necessary to define compliance acceptance levels for the prescribed indoor air limits. The use of comfort or environmental indexes could be of considerable help to ameliorate the evaluation of IAQ. This paper presents a proposal of an index regarding IAQ which considers both the aspects of thermal comfort and non-toxicity. The proposed index was calculated for offices of several European countries, available from previous studies and for Portugal as well. Bearing in mind there is few existing data, this study is consistent with the proposed index, as the obtained values are similar to Greece, which has several similarities with the Portuguese situation.